PEMBERDAYAAN GURU DALAM MENINGKATKAN ORAL HYGIENE ANAK R.A ANTASSALAM KOTA TASIKMALAYA MELALUI APLIKASI YUMMY - Rismayani, Lina; Kamelia, Emma; Dewi, Tita Kartika (Jurnal Abdimas Bina Bangsa, 2024)
This community service project aimed to empower teachers in improving the oral health of preschool children through the utilization of the "Yummy" mobile application. The activity was conducted at RA Antassalam in Tasikmalaya City, involving 7 teachers and 33 preschool children. The methods employed included teacher training, introduction to the Yummy application, practical sessions with children, and pre- and post-intervention evaluations. Results showed significant improvements in teachers' knowledge and skills in promoting children's dental health, and children's oral hygiene improved to good levels. The use of the Yummy application as an interactive educational tool proved effective in enhancing children's enthusiasm and understanding of oral hygiene. This program not only increased short-term capacity but also aimed to instill habits and awareness of the importance of oral health from an early age. This innovative approach is expected to have a lasting positive impact on the oral health of children at RA Antassalam in Tasikmalaya City.